Проблема вичерпності мінерально-сировинних ресурсів у контексті забезпечення сталого надрокористування - Пугач, В.О. (Економіка природокористування і охорони довкілля, 2015)
Розглядаються основні аспекти та підходи до визначення сталого надрокористування. Обґрунтовано, що основною проблемою його забезпечення є вичерпність мінерально-сировинних ресурсів. Як основний механізм подолання останньої наведено правило Хартвіка, за яким рентні платежі повинні спрямовуватися у відтворювальний капітал для підтримання реального споживання. Доведено, що сума рентних платежів має визначатися індивідуально для кожного окремого випадку, враховуючи інтереси всіх зацікавлених сторін: держави, суспільства та бізнесу. Визначено, що реінвестування рентних платежів в інші форми капіталу – людський, технологічний, природний, фінансовий забезпечить умови для сталого надрокористування. The article investigates the main aspects and approaches to the definition of sustainable using of mineral resources. Sustainable using of mineral resources - a process to ensure effective use of subsoil for mining, or other tasks provided by the law, in a balanced interaction between the state, business and society with environmental safety based on the reinvestment of revenues from the extraction of mineral resources into other forms of capital. The main challenges to sustainable mineral resources can be considered exhaustion of mineral resources and irreversible adverse impact on the environment. Solving the problem of exhaustion of resources, in our opinion, makes the concept of John M. Hartvik. Society should invest rental income from the exploitation of non-renewable resources in reproductive capital to maintain the real consumption. Nothing rental income should be consumed current generation. Subsoi use must take place in conditions of effective cooperation between the state, business and society. With expert studies and assessments should be determined the amount of rent payments. Determined that based on the rent payments and their reinvestment in other forms of capital, particularly for exploration, will ensure stable functioning of the mineral industry.